2011
DOI: 10.1111/j.1751-7893.2011.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Group programmes in early intervention services

Abstract: Social functioning and vocation are important considerations in facilitating young people's recovery from mental illness. Such issues can be addressed within the context of psychosocial recovery group programmes. Further research is needed not only to address problems regarding client engagement but also to evaluate outcomes from participation in such programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Previous research has stated that programmes that include social relations, such as group‐based education, represent a good nursing strategy to provide tools to improve health and recovery (Cotton et al . ; Fiorillo & Sabatini ; Knutson et al . ), but reports about this type of intervention directed at young adults with mental illness in primary health care are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has stated that programmes that include social relations, such as group‐based education, represent a good nursing strategy to provide tools to improve health and recovery (Cotton et al . ; Fiorillo & Sabatini ; Knutson et al . ), but reports about this type of intervention directed at young adults with mental illness in primary health care are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been suggested that increased involvement and having access to the same knowledge as the staff are important aspects to promote recovery and healthy lifestyle habits . Furthermore, social interaction is considered a good nursing strategy; also, in the present program, social relationships emerged as a key factor.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we have reported that those who do not attend PRGP are more likely to have a psychotic disorder, are older, unemployed, have substance use issues and have difficulty with peer relationships. 13 Clients attend groups on the basis of their interests, goals and developmental needs. 13 Those who participate in OAG are drawn from the same pool of PRGP participants.…”
Section: Discussionmentioning
confidence: 99%
“…12 The group timetable is run over an 8 to 10-week school term. The PRGP adopts a strength-based approach and utilizes collaborative goal setting, where young people attend groups according to their personal goals, interests and developmental needs (for further description of PRGP and sample timetable, see Cotton et al 13 ).…”
Section: Participants and Settingmentioning
confidence: 99%